Iman Berakar dalam Keluarga dan Implikasinya pada Pendidikan Karakter Anak - Sitepanus Zebua (Jurnal Magistra, 2026)
This study aims to examine how faith rooted in the family has implications for children's character education. The family is the first and foremost environment in human life, where children begin to learn about life values, including faith, morals, and responsibility. In Christian families, parents play a crucial role in instilling and fostering faith through living examples, praying together, and participating in Church life. This study employed a qualitative research method with a descriptive approach. The analysis was conducted by reviewing various scientific sources and Church documents relevant to the research theme, such as Familiaris Consortio and Amoris Laetitia, which emphasize the role of the family as a "domestic Church." The documents of the Second Vatican Council, as well as relevant journals and books, were also used. The results of the study indicate that faith that lives and grows within the family has a significant influence on the formation of children's character. The values ​​of faith taught within the family, such as love, honesty, responsibility, and concern for others, form an important foundation for developing good character. Through consistent faith education within the family, children can grow into individuals with faith, morals, and the ability to live responsibly in society.